Market Reaction on the Announcement of Elected President (The 2019 Presidential Election in Indonesia) - Fidiana Fidiana (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2020)
Investors tend to respond to political events information because they are considered to be supporting or risking the stability of the capital market, so they must immediately make investment decisions quickly. Unlike the election process in other countries, this five-yearly election in Indonesia is not just a regularity of changing authorities but also carries an ideological gamble. The 2019 election as a necessary test for Indonesia related to the issue of communist phobia: between secular and conservative. Different from previous research on political events that focus on the electoral period, this study aims to prove the information content of the presidential announcement in 2019 by using a window period of eleven days, which is five days before and five days after the announcements. Tests were conducted on 45 companies registered as LQ-45 companies in 2019. Different samples of paired tests were done using a paired t-sample tool by comparing abnormal returns and the level of stock trading activity. By using various tests, this study proves the existence of significant differences in abnormal returns and trading activities in the period before and after the 2019 presidential announcement. So, it was concluded that the 2019 presidential announcement had information content that had an impact on obtaining abnormal returns for investors. This study also proves that investors respond to information and political events as part of their investment decisions. So that daily transaction fluctuations are indicated by a trend of increasing and decreasing selling and buying actions on a spot time.